China's Hong Kong : the politics of a global city - Summers, Tim (Business with China., 2019)
At a time of heightened tensions in Hong Kong, this book offers a balanced and clear-headed appraisal of the politics of this global city. The constitutional settlement under which Hong Kong became a Special Administrative Region of the PRC in 1997 was based on the idea of "one country, two systems". At the time of Hong Kong's handover from British to Chinese rule, there was much speculation over how and whether an open society and market economy would be respected by an authoritarian state, one which has since risen to become the world's second largest economy. Since the protests and street occupations over the issue of democracy in 2014, and the massive protests of June 2019, Hong Kong is firmly back in the news. Tim Summers looks afresh at the constitutional settlement and considers whether it has been able to withstand the changes in Hong Kong, the economic rise of China, and the shifts in the global economy that have accompanied them. He argues that the developments in Hong Kong have to be understood as a unique interplay between local, national and global developments and challenges the assumption that the main dynamic at work in Hong Kong is its tussle for control with Beijing